Strengthening Legal Protection for Construction Service Providers Amid Corruption and Legal Uncertainty - Ratnasari, Yeni; Gunarto; Mashdurohatun, Anis (Research Horizon, 2025)
This study analyzes the legal protection for building construction service providers amid corruption in state infrastructure projects. It highlights the significant issue of budget misuse in corruption cases, as reported by Indonesia Corruption Watch (ICW) in 2022. A major obstacle is the inadequacy of Law Number 2 of 2017, which fails to sufficiently protect construction service providers who primarily act as implementers without control over the budget. Additionally, the law removes criminal penalties for failure to complete projects, causing legal uncertainty and violating the principle of justice in the 1945 Constitution. Using a sociological juridical approach, the findings suggest a need to revise regulations to clearly separate the responsibilities of construction providers and budget authorities. For Indonesia to strengthen its legal system based on Pancasila and justice, the research calls for regulatory reforms to protect construction service providers from legal exploitation and ensure a more coherent national legal framework.